PCB Defect Detection Using Deep Learning Techniques - Jangama Viswanath; S.Munikumar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The detection of Printed Circuit Board (PCB) defects plays a critical role in ensuring the quality and reliability of electronic products. This project focuses on automating the process of identifying various types of PCB defects such as missing holes, mouse bites, open circuits, shorts, spurs, and spurious copper using state-of- the-art deep learning techniques. YOLOv8, a highly efficient and accurate object detection model, is utilized to detect and classify these defects from PCB images. The system is powered by Google Colab, leveraging its computational capabilities for deep learning model training, while the user interface is developed using Streamlit, providing a seamless and interactive experience. By automating the defect detection process, the system not only enhances the speed and accuracy of quality control but also reduces the potential for human error, significantly improving productivity in PCB manufacturing. This project offers promising solutions for high-volume production environments, ensuring that only high-quality electronic components are produced.